Sterically Hindered 2‐(2'‐Hydroxyphenyl)benzoxazole (HBO) Emitters: Synthesis, Spectroscopic Studies, and Theoretical Calculations. Issue 30 (9th August 2022) - Stoerkler, Timothée; Pariat, Thibault; Laurent, Adèle D.; Jacquemin, Denis; Ulrich, Gilles; Massue, Julien
Abstract: We describe various synthetic pathways to introduce sterically hindered substituents (mesityl, 2, 4, 6‐triisopropylphenyl, anthracene) to the proton donor side of excited‐state intramolecular proton transfer (ESIPT)‐capable 2‐(2'‐hydroxyphenyl) benzoxazole (HBO) fluorophores. Two original synthetic approaches were investigated in order to synthesize seven HBO derivatives. Optimization studies concluded that electron rich and bulky phosphine ligands are required to ensure completion of the Suzuki‐Miyaura cross‐coupling reaction involving a bulky aromatic boronic acid. The photophysical properties of all dyes revealed a strong influence of the nature of the solvent on the optical properties, as protic solvents tend to stabilize enol tautomers and induce dual emission. Our studies confirmed that, unlike the majority of organic dyes, ESIPT fluorophores do not undergo π‐stacking in the solid‐state. The nature of the excited‐states was explored by ab initio calculations. Abstract : Seven original fluorophores, based on the 2‐(2'‐hydroxyphenyl) benzoxazole scaffold, containing sterically‐hindered groups such as mesityl are reported. The full photophysical investigation evidenced a complete absence of π‐stacking in the solid‐state, as a result of a quantitative proton transfer process in the excited‐state. Ab initio calculations rationalized the nature of the excited‐states.